Efficacy of 2% Hydroxypropyl Methylcellulose and Bandage Contact Lens for the Management of Dry Eye Disease after Cataract Surgery - Tianyao Zhao; Xiaodan Jiang; Ran Hao; Yi Ding; Dalan Jing; Xuemin Li (Journal of Ophthalmology)
Objectives. To investigate the effect of 2% hydroxypropyl methylcellulose (HPMC) and bandage contact lens (BCL) on dry eye disease after cataract surgery. Methods. This prospective randomized controlled trial included 63 eyes which were divided into the balanced salt solution (BSS), HPMC, BCL, and combined HPMC and BCL (H&B) groups. The Ocular Surface Disease Index (OSDI), tear meniscus height (TMH), and average tear break-up time were measured before cataract surgery and 30 days postoperatively. Differences in corneal nerve fiber (CNF) and dendritic cell (DC) density in various directions were evaluated and compared. The CNFs and DCs in central and infratemporal directions were observed using in vivo confocal microscopy. Data were evaluated using the Kruskal–Wallis rank-sum test and analysis of variance. Results. The differences in variations in OSDI and TMH after cataract surgery between the four groups were statistically significant (P<0.05). The postoperative OSDI of the HPMC group decreased compared with their preoperative OSDI. A statistically significant difference in the variations of OSDI score was observed between the HPMC and other groups (P<0.05). The postoperative variations in TMH in the HPMC group were significantly higher than those observed preoperatively and significantly differed between HPMC and BCL groups and between BCL and H&B groups (P<0.05). Postoperatively, the density of corneal DCs decreased in BSS and HPMC groups and increased in BCL and H&B groups (P<0.001). Conclusions. The application of 2% HPMC in cataract surgery has a certain effect on managing dry eye after cataract surgery. Although the use of BCLs after cataract surgery has some benefits, it may cause mild ocular surface inflammation. Nevertheless, using 2% HPMC with BCLs in the perioperative phase of cataract surgery can alleviate the subjective discomfort of patients and can safely and effectively replace eye patch after cataract surgery.